Graphene oxide thin film structural dielectric capacitors for aviation static electricity harvesting and storage. (15th November 2020) - Chan, Kit-Ying; Pham, Duy Quang; Demir, Baris; Yang, Dan; Mayes, Edwin L.H.; Mouritz, Adrian P.; Ang, Andrew S.M.; Fox, Bronwyn; Lin, Han; Jia, Baohua; Lau, Kin-Tak
Abstract: In this paper, we demonstrate the feasibility of using carbon fibre reinforced polymer (CFRP) laminates for the dual functions on aircraft as high load-bearing structural materials as well as for the harvesting and storage of static electricity during flight which can be used to power navigation lights and other electrical systems. CFRP laminate was fabricated into a structural dielectric capacitor (SDC) composite by sandwiching graphene oxide (GO) film between two electrically-conductive carbon fabric layers. To meet the high requirements of aviation applications, the mechanical properties of the GO-based SDC composite were increased using a polymer cross-linking agent in the GO film. This work opens a new concept and possibility of converting the safety threatening static charges into useful electrical energy, which not only reduces the safety hazard, but also improves the energy efficiency of aircraft without compromising the mechanical performance.